Effect of levosimendan combined with recombinant human brain natriuretic peptide on diuretic resistance. Issue 1 (1st January 2021) - Xiangli, Shen; Lan, Li; Libiya, Zu; Jun, Ma; Shubin, Jiang
ABSTRACT: Levosimendan is a calcium sensitizer used for managing heart failure (HF) because of its inotropic and vasodilatory effects. As many patients do not respond to levosimendan as a monotherapy, it may be necessary to combine it with other diuretic agents such as recombinant human brain natriuretic peptide (rhBNc P). The aim of this study was to investigate efficacy of levosimendan when combined with rhBNP in patients with diuretic resistance and low ejection fraction (EF) rate. The study included HF patients with diuretic resistance and low EF. Before grouping, patients with a 24-hour urine volume of <0.5 mL/kg/h were administered with furosemide injection. Treatment group was administered levosimendan injection based on the original diuretic and rhBNP. One hundred twenty-eight patients were included, with 64 patients each in the control and treatment arms. 24-hour urine volume of the treatment group was significantly higher than that of the control group. Moreover, dyspnea score of the treatment group significantly improved compared with control group. In the treatment group, 12.5% of patients had no significant changes in the urine volume, weight, and dyspnea score before and after the treatment, indicating poor curative effect of the treatment, whereas in the control group, 23.4% of patients had poor curative effect ( P < .05). No significant change was observed in the systolic blood pressure, heart rate, and serum creatinine level before and after treatment in both groups. Levosimendan in combination with rhBNP can effectively relieve diuretic resistance, reduce body weight, improve dyspnea, and ensure safety in the treatment process.